THE EFFECTIVENESS OF THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF JIGSAW TYPE USING PROBLEM POSING-SOLVING APPROACH AT SMPN 26 MAKASSAR - Kiswanto, Kiswanto (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The research aims to discover the effectiveness of the implementation of cooperative learning model of jigsaw type using problem posing-solving approach in class VIII at SMPN 26 Makassar. The research is pre-experimental research. The populations of research were all of the students of class VIII at SMPN 26 Makassar and the sample was class VIII 5 as the experiment class cosen by using cluster random sampling technique. The data of the research were collected by using instruments, namely learning implementation observation sheet, student’ activities observation sheet, learning result test, and student’ responses questionnaire. The data of the research were analyzed by using descriptive and inferential analysis. The results of research reveal that both descriptively and inferentially, the cooperative learning model of jigsaw type using problem posing-solving approach had met effective criteria, where descriptively the students’ activities in learning is in active category with the average score 3,5, the student’ mathematics learning result is in high category with the mean score 81,39, and deviation standart 9,21, completeness proportion level classically is 0,86, the average of normalized gain of learning results is in high category, the student’ responses on the implementation of cooperative learning model of jigsaw type using problem posing-solving approach are in tended to be positive category with the average score 3,36. In generally, it is concluded that the implementation of cooperative learning model of jigsaw type using problem posing-solving approach is effective to be implemented in class VIII at SMPN 26 Makassar